2016
DOI: 10.1149/2.0831609jes
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Current Density Distribution in the Land-Channel Direction of a PEMFC

Abstract: A proton exchange membrane fuel cell (PEMFC) was segmented to measure local current density, electrochemical surface area, and high frequency resistance (HFR) distribution in the land-channel direction at resolution of 350 μm. An in-house catalyst coated membrane of 3 mm × 3 mm active area was prepared to represent a small area in a larger scale cell with 1 mm land and channel widths. This design was employed to measure current density and HFR distribution at 60 • C with several different operating conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…The 2D-distributions of variables Γ i = ch,a , RH ach/acl , RH cch/ccl , mem and acl/ccl , as well as the 2D-distributions of current density and membrane ionic resistance, were calculated as: Sánchez et al [19], the pressure drop along the anode channel, ∆ g,ach , increases from 0.96 kPa to 1.44 kPa during current ignitions due to the blockage exerted by liquid water on the hydrogen flow. In contrast, the cathode stream remains undersaturated in both performance states, as shown by the neutron visualizations (see, e.g., the absence of water in the cathode channel in Figure 1(b RH a in = 50%, RH c in ≈ 0%), they found that higher current densities are generated under the ribs due to the better membrane hydration achieved in this region [100].…”
Section: Numerical Results (Baseline Case)mentioning
confidence: 86%
“…The 2D-distributions of variables Γ i = ch,a , RH ach/acl , RH cch/ccl , mem and acl/ccl , as well as the 2D-distributions of current density and membrane ionic resistance, were calculated as: Sánchez et al [19], the pressure drop along the anode channel, ∆ g,ach , increases from 0.96 kPa to 1.44 kPa during current ignitions due to the blockage exerted by liquid water on the hydrogen flow. In contrast, the cathode stream remains undersaturated in both performance states, as shown by the neutron visualizations (see, e.g., the absence of water in the cathode channel in Figure 1(b RH a in = 50%, RH c in ≈ 0%), they found that higher current densities are generated under the ribs due to the better membrane hydration achieved in this region [100].…”
Section: Numerical Results (Baseline Case)mentioning
confidence: 86%
“…3, p (O2) was seen to decrease from the inlet to the outlet, but not always monotonically along the flow channel because of the cross flow through the GDL as reported previously. 33) p (O2) under the ribs was clearly observed, and the value was lower than that under the neighboring flow channel because of the lower gas diffusivity under the ribs 3) ,5) , 8) The insufficient diffusivity should have lowered the oxygen concentration and increased the water vapor pressure. As the Uo2 increased, p (O2) near the inlet was also seen to increase.…”
Section: Resultsmentioning
confidence: 96%
“…Decal transfer method was used to prepare an MEA. Nafion membrane (25 μm, NRE-211, DuPont, Wilmington, DE, USA) was hot-pressed in between the anode (0.2 mg Pt /cm 2 ) and the cathode decals at 150 °C and 2 MPa pressure for 3 min [ 44 , 45 ]. The MEAs had an anode and cathode active area of 1.44 and 1 cm 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%